Exploration of Secondary Metabolite from Endophytic Microorganisms in Java Ginseng Root as Antifungals - Windiastuti, Erviyana; Wahyuni, Sri; Manik, Visi Tinta; Sunarya, Yaya; Hartini, Elya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The emergence and spread of pathogens is one of agriculture's problems. Rhizopus stolonifer is the pathogen to be on the lookout for because it causes rhizopus loose rot disease. The pathogen must be dealt with immediately because it can result in losses of up to 40%. Integrated plant disease management (IPDM) is the approach being promoted. The application of biological agents or biocontrol is one solution that supports IPDM. The challenge is met by biological agents through the production of secondary metabolites. The endophytic microorganisms found in Java ginseng (Talinum triangulare) are one source of secondary metabolites. Thus, the purpose of this study was to investigate whether endophytic microorganisms in Javanese ginseng roots have the ability to combat the pathogen R. stolonifer. The experimental method involved analyzing the secondary metabolite from the endophytic microorganism in ginseng in vitro. phytochemical and zone of inhibition were the two types of test that were being performed. The obtained result was a set of extract that contains triterpenoid and alkaloid. In addition, extract B (FN-1) had the strongest inhinbitiom zone against R. stolonifer.